2018
DOI: 10.2174/1874944501811010135
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of HIV Load Suppression and Related Factors Among Patients on ART at Phedisong 4 Clinic, Pretoria, South Africa

Abstract: Background:Globally, the benefits of viral load suppression in improving the lives of people living with HIV/AIDS have been established. In 2010, the South African Government decentralised ART to the primary care level. This study intended to determine the effect of this decentralisation in achieving viral load suppression among patients. Objective:To determine the prevalence of HIV viral load suppression and factors related to the suppression among patients initiated on ART at Pedisong 4 clinic, Tshwane Distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 40 publications
5
10
3
Order By: Relevance
“…Nonetheless, educational level was not associated with viral suppression. This finding concurs with studies done in SA, 17 Spain 25 and Uganda. 26 In contrast, other studies have shown lower educational level to be associated with unsuppressed VL.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Nonetheless, educational level was not associated with viral suppression. This finding concurs with studies done in SA, 17 Spain 25 and Uganda. 26 In contrast, other studies have shown lower educational level to be associated with unsuppressed VL.…”
Section: Resultssupporting
confidence: 93%
“…= 10.3). Age was not associated with viral suppression, in keeping with findings of a study done in Ga-Rankuwa, SA, by Mogosetsi et al 17 However, some studies have shown that younger age of less than 35 years was associated with unsuppressed VL, 18,19 whilst older age was more likely to achieve suppressed VL. 20,21 In our study, females were in the majority (72.9%).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations